Rainfall data adjustment to Volta Redonda macro-region - Thaner dos Santos, Hugo; Nascimento Duarte, Sergio (Revista Brasileira de Engenharia de Biossistemas, 2023)
Most Brazilian cities do not have a proper water and soil management system due to lack of planning in this sector and of an easy-consultation local-hydrological bibliography capable of reinforcing the future creation of a hydrological modeling. Volta Redonda macro-region’s case can be added to this statistics, since it accounts for several natural hazards linked to floods and inundations in some specific locations. The aims of the present study are to descriptively analyze monthly rainfall data generated by CEMADEN’s rainfall gauges and to assess whether monthly rainfall in the region adapts well to probability Gamma Distribution plots. Rainfall data from four points in Volta Redonda, Barra Mansa and Pinheiral cities, recorded for 48 months, and provided by CEMADEN, were used in the study. Gamma Distribution was adjusted to monthly rainfall data. In conclusion, the probability of having a given monthly rainfall value lower than, or equal to, that recorded for the Pinheiral – Volta Redonda – Barra Mansa conurbation area can be estimated through Gamma Distribution. Values recorded for shape (γ) and scale (β) parameters of Volta Redonda macro-region’s municipalities were 1.59 and 79.30, on average, respectively.